The benefit of early acupuncture within 7 days for neurological outcomes in ischemic stroke patients after cardiac surgery - Chia-Hsuan Kuan; Chi-Nan Tseng; Tse-Hung Huang; Chien-Chung Yang; Yu-Sheng Chen (Perioperative Medicine)
Abstract Background Stroke is a critical complication of cardiac surgery that results in increased mortality and morbidity. Limited treatment options are available for patients with severe neurological deficits, such as impaired consciousness. Acupuncture is a well-known integrative management method for stroke patients. However, there are no extensive reports discussing the benefit of acupuncture in stroke patients after cardiac surgery. The aim of this study was to demonstrate the role of acupuncture in the neurological recovery of these patients and to identify the factors that provide greater benefit. Methods This self-controlled case series utilized inpatient data from stroke patients after cardiac surgery who received acupuncture in a single center from 2013 to 2019. The primary outcomes included the Glasgow Coma Scale, muscle strength grading scale, and Barthel Index. Wilcoxon signed-rank test was used to compare the neurological differences between pre-acupuncture and post-acupuncture. Results Fifty-one patients who met the criteria showed significant improvement of the severity of neurological impairment, including the Glasgow Coma Scale, muscle strength grading scale, and Barthel Index (p < 0.05). The group that underwent aortic dissection repair and the group that started acupuncture within 7 days after stroke showed greater improvement (p < 0.01). No adverse events were reported. Three patients with profound neurological impairment who received acupuncture intervention were described. Conclusions Acupuncture has a potential benefit in improving neurological impairment and reducing mortality in stroke patients after cardiac surgery, especially within 7 days of the event. Further larger prospective studies with control groups are needed to provide convincing evidence.